Ekstrak Etanol Kulit Buah Naga Menurunkan Indikasi Neoplasia Mammae Tikus Putih Berdasarkan Histopatologi dan Inhibitor Siklooksigenase-2 - Purnama, Muhammad Thohawi Elziyad; Prastiya, Ragil Angga; Fikri, Faisal; Saputro, Amung Logam; Agustono, Bodhi (Jurnal Veteriner, 2018)
Cancer caused uncontrolled cell proliferation and triggered by changes on cell information that regulate growth function. Each cell has different potential so many cancer prevalence such as endometrial cancer, lymph node cancer, lung cancer, skin and mammary gland cancer. The aims of this study were to assess the potential of dragon fruit skin ethanolic extract on white rats ( Rattus norvegicus ) exposed 7,12- Dimethylbenz(á)antrasena (DMBA) on mammary gland based on histopathological features and cyclooxygenase-2 (Cox-2) intensity. This study were used 20 of rats randomly divided into five group and each groups consisted of four rats, i.e: K+ weren’t treated DMBA and extract; K- were treated with DMBA; P1 were treated with DMBA and extract 10 mg/kg BW; P2 were treated with DMBA and extract 15 mg/kg BW; P3 were treated with DMBA and extract 20 mg/kg BW. The DMBA was given by intra dermal injection during twice a week for five weeks and the extracts with gastric tube everyday till 14 days. The data was analyzed by Anova test and continued with Duncan test. The result showed that the histopathological features were decrease significantly on P3. The variables of Cox-2 intensity were decrease significantly on P1, P2 and P3. Conclusion of this study was ethanol extract of dragon fruit skin can decrease neoplastic indication of mammary gland on white rats ( R. norvegicus ) based on histopathological features and Cox-2 inhibitors.